(untitled) (American International Journal of Economics and Finance Research, 2020)
This study examined how cash flow management and human capital investment affect capital gain of commercial banks in Nigeria. Cross sectional data were sourced from the financial statement of the commercial banks from 2009 to 2018. Capital gain was used as dependent variables while investment on employee training, investment on employee education, investment on employee health, differed employee payment, operating cash flow, cash flow from financing activities, cash flow from investing activities and net cash flow were used as independent variables. Ordinary least square method of panel co-integration, unit root, granger causality test was used. The study found among other things that operating cash flow, cash flow financing activities and cash flow from investing activities showed negative relationship with capital gain while net operating cash flow showed positive relationship with capital gain. Investment on employee training and health has positive relationship with capital gain while differed payment and education has negative relationship with capital gain. From the findings, the study concludes that cash flow management and human capital investments have significant effect capital gain of commercial banks in Nigeria. We that management of commercial banks should investment more on employee education as this can make the employees acquire dynamic knowledge in bank management such as credit appraisal that reduces the incidence of nonperforming loans and increase profitability. Furthermore, employees differed payment procedures should be well planned and seamlessly integrated into management broad policies of investment and financing decisions.